Forced male circumcision and the politics of foreskin in Kenya. Issue 2 (3rd April 2018) - Lamont, Mark
ABSTRACT: Do forced male circumcisions have political legitimacy in Kenya that they do not have internationally? This article asks what these acts of public violence tell us about the relationships between moral ethnicity and state formation in Kenya. It examines the place of intermarriage and migration as factors to consider in this violence. Forced male circumcision highlights certain ambivalence towards human rights in Kenya that should not be ignored by observers of African pluralism and constitutional reform. Amid a generalised crisis of masculinity, forced circumcisions raise important questions about human rights processes and different kinds of social authority. This focus on forced circumcision brings to the surface historically layered understandings of citizenship, masculinity, and gender violence.